Returns of provisions, small stores & clothing, at the Gosport Navy Yard, April 1861 : March 31 1862 (Document (Virginia. General Assembly. Senate) ;, 1862)
March 31, 1862 Communication of Governor Letcher to the General Assembly regarding the returns of provisions, small stores and clothing at the Gosport Navy Yard as of April 20, 1861. Of note, the governor indicated that the larger portion of same were transferred to the Confederate government under the convention between the two governments.